Intraoperative Assessment of Margins in Breast Conserving Therapy: A Systematic review - Butler-Henderson, K.; Lee, Andy; Price, R.; Waring, K. (Churchill Livingstone, 2014)
Approximately one quarter of patients undergoing breast conserving therapy for breast cancer will require a second operation to achieve adequate clearance of the margins. A number of techniques to assess margins intraoperatively have been reported. This systematic review examines current intraoperative methods for assessing margin status. The final pathology status, statistical measures including accuracy of tumour margin assessment, average time impact on the procedure and second operation rate, were used as criteria for comparison between studies. Although pathological methods, such as frozen section and imprint cytology performed well, they added on average 20e30 min to operation times. An ultrasound probe allows accurate examination of the margins and delivers results in a timely manner, yet it has a limited role with DCIS where calcification is present and in multifocal cancer. Further research is required in other intraoperative margin assessment techniques, such as mammography, radiofrequency spectroscopy and optical coherence tomography.